Building capacity from within: qualitative evaluation of a training program aimed at upskilling healthcare workers in delivering an evidence-based implementation approach. Issue 1 (13th July 2021) - Morrow, April; Chan, Priscilla; Tiernan, Gabriella; Steinberg, Julia; Debono, Deborah; Wolfenden, Luke; Tucker, Katherine M; Hogden, Emily; Taylor, Natalie
Abstract: Translating evidence into complex health systems is an ongoing challenge. Building the capacity of healthcare workers in behavioral and implementation science methods may facilitate the use of evidence-based implementation approaches, leading to sustainable and effective translation. The aim was to describe the development, contents and evaluation of a training workshop aimed at upskilling hospital-embedded staff to deliver an evidence-based implementation approach. The Hide and Seek Project ( HaSP ) is a cluster randomized controlled trial testing two implementation approaches for improving hereditary cancer referral at eight Australian hospitals. Healthcare workers were recruited as "Implementation Leads" and trained via a one-day workshop—TRAining in evideNce-baSed ImpLementATion for hEalth (TRANSLATE). The purpose of TRANSLATE was to upskill Implementation Leads in the delivery of HaSP, as well as implementation science methods more broadly. Implementation Leads participated in semi-structured evaluation interviews, which were analyzed using inductive thematic analysis. Nine Implementation Leads from various professional backgrounds completed the training. Four key themes were identified: (i) training day reactions, (ii) learning, (iii) implementation barriers and facilitators, and (iv) building health system capacity for implementation. Participants reported high levels of satisfaction, and anticipated that the knowledge and skills may be useful in the future. We describe a novel training program focused on the delivery of evidence-based implementation within health systems. Guided by insights from this study, methods to deliver the training on a larger scale and across different contexts are being explored. The prolonged impact of TRANSLATE will be further evaluated at trial completion. Trial registration : ANZCTR, ACTRN12618001072202. Registered on June 27, 2018